Efficient fabrication of high strength Li2TiO3 ceramic pebbles via improved rolling ball method assisted by sesbania gum binder. Issue 19 (1st October 2021) - Tan, Guangfan; Song, Shihao; Hu, Xin; Cai, Liang; Li, Yusha; Zhang, Yingchun
Abstract: In this work, a method combining the spray-drying process and rolling ball method was first selected to mass fabricate Li2 TiO3 tritium breeder ceramic pebbles. Herein, we overcome the issues namely complex production, high manufacturing cost, and lower mechanical strength in previous reports. The Li2 TiO3 powder with high packing density after the spray drying process will self-agglomerate to form denser structured pebbles during the rolling ball process assisted by sesbania gum binder solution. The stability of slurry, different binder, binder concentrations, the formation mechanism, and the morphology of green pebbles were investigated by using viscometer, SEM. Moreover, the force on the Li2 TiO3 green pebbles was also analyzed during the rolling ball process. After the debinding and densification process, the Li2 TiO3 pebbles have a uniform diameter of 1.2 mm and good sphericity of 0.97. The Micro-CT instrument showed that the internal structure of the Li2 TiO3 pebbles was dense. The experiment's confirmation shows that the Li2 TiO3 ceramic pebbles sintered at 1000 °C have optimal mechanical properties such as a crushing load of 108 N and relative density of 92.4%TD, which is much larger than that of the pebbles obtained using traditional methods. This work not only overcomes the core-shell structure but also provides a new platform for better mechanical properties for studying the other materials systems in the future.